(untitled) (Acta Entomologica Serbica, 2021)
The manuscript encloses the first finding of the leafhopper Arboridia kakogawana (Hemiptera: Auchenorrhyncha: Cicadellidae: Typhlocybinae) in Serbia. On total of four sites in Vojvodina, identification based on the morphological characters gave us data on the presence of this allochtonous species that was previously detected in Romania and Crimean peninsula. Arboridia kakogawana is known as the grapevine pest and it was observed in Serbia on two localities on damaged grapevine plants expressing characteristic symptoms of its presence such as intensive chlorotic patches. Individuals were collected using entomological nets and light traps.